Manipulating music to communicate automation reliability in conditionally automated driving: A driving simulator study. Issue 145 (January 2021) - Chen, Kuan-Ting; Chen, Huei-Yen Winnie
Highlights: Music feedback on automation reliability increased monitoring in automated driving. Music feedback on automation reliability supported takeover in automated driving. Blended sonification has the potential to improve automation transparency. Blended sonification has the potential to help keep drivers on the loop. Abstract: With increasing vehicle automation, drivers are likely to engage in non-driving related tasks. However, before fully autonomous vehicles can be achieved, drivers remain the fallback when automation limits are reached and/or in unexpected situations. Transition from automated to manual control could be particularly difficult for drivers who are "out-of-the-loop". To support safe and smooth control transition, we adopted the blended sonification approach in manipulating background music to convey information about the reliability level of the automation. A driving simulator study consisting of 36 participants was conducted to investigate the effectiveness of sonification feedback—three levels of system reliability was mapped to background music pitch levels—on takeover events. Participants were assigned to one of three groups that received continuous sonification feedback, intermittent sonification feedback, or no feedback about automation reliability. The proposed blended music sonification was found effective in increasing monitoring behavior and decreasing visual response times to takeover requests during automated driving. Steering control in a takeover scenario that required substantial amount of maneuvering also benefitted from having sonification feedback. There was some evidence that sonification feedback provided continuously was more effective than when it was provided intermittently, possibly related to observed differences in the associated glance patterns. In conclusion, blended sonification may be an effective approach in helping drivers stay on the loop during automated driving, although the study was limited to the choice of music examined. Our future work will investigate how best to combine automation reliability information and traffic situational information to better support situation awareness and facilitate task-switching in automated driving.